Black Patients Have Unequal Access to Listing for Liver Transplantation in the United States. Issue 3 (15th September 2021) - Rosenblatt, Russell; Wahid, Nabeel; Halazun, Karim J.; Kaplan, Alyson; Jesudian, Arun; Lucero, Catherine; Lee, Jihui; Dove, Lorna; Fox, Alyson; Verna, Elizabeth; Samstein, Benjamin; Fortune, Brett E.; et al.
Abstract : Background and Aims: The Model for End‐Stage Liver Disease score may have eliminated racial disparities on the waitlist for liver transplantation (LT), but disparities prior to waitlist placement have not been adequately quantified. We aimed to analyze differences in patients who are listed for LT, undergo transplantation, and die from end‐stage liver disease (ESLD), stratified by state and race/ethnicity. Approach and Results: We analyzed two databases retrospectively, the Center for Disease Control Wide‐ranging Online Data for Epidemiologic Research (CDC WONDER) and the United Network for Organ Sharing (UNOS) databases, from 2014 to 2018. We included patients aged 25‐64 years who had a primary cause of death of ESLD and were listed for transplant in the CDC WONDER or UNOS database. Our primary outcome was the ratio of listing for LT to death from ESLD—listing to death ratio (LDR). Our secondary outcome was the transplant to listing and transplant to death ratios. Chi‐squared and multivariable linear regression evaluated for differences between races/ethnicities. There were 135, 367 patients who died of ESLD, 54, 734 patients who were listed for transplant, and 26, 571 who underwent transplant. Patients were mostly male and White. The national LDR was 0.40, significantly lowest in Black patients (0.30), P  < 0.001. The national transplant to listing ratio was 0.48, highest in Black patients (0.53), P  < 0.01. The national transplant to death ratio was 0.20, lowest in Black patients (0.16), P  < 0.001. States that had an above‐mean LDR had a lower transplant to listing ratio but a higher transplant to death ratio. Multivariable analysis confirmed that Black race is significantly associated with a lower LDR and transplant to death ratio. Conclusions: Black patients face a disparity in access to LT due to low listing rates for transplant relative to deaths from ESLD.